2008
DOI: 10.1262/jrd.20018
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Development of Mouse Pronuclear Embryos to Blastocysts in Sequential Media With and Without Co-Culture of Autologous Cumulus Cells

Abstract: Abstract. The objective of this study was to use mouse embryos as a model system to investigate the effect of co-culture of cumulus cells in Sydney IVF sequential media (Cook) on embryo development, based on the hypothesis that feeder cells in co-culture with a sequential medium could work synergistically to further improve in vitro culture conditions for mammalian preimplantation embryos. The culture systems described here were evaluated by the ability to consistently produce high blastocyst formation rates a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 45 publications
(52 reference statements)
0
12
1
Order By: Relevance
“…In contrast to our suggestion, some authors have proposed; addition of embryotrophic substances which are usually secreted by the somatic cells into the simple culture media, may improve embryo quality without the need of feeder cells [33,40]. However, recent studies have shown a direct contact between the embryo and feeder cells enhance embryo development better than the embryos cultured in presence of feeder cells without a direct contact [18]. Besides, this assumption may be true if the negative conditioning hypothesis was neglected.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…In contrast to our suggestion, some authors have proposed; addition of embryotrophic substances which are usually secreted by the somatic cells into the simple culture media, may improve embryo quality without the need of feeder cells [33,40]. However, recent studies have shown a direct contact between the embryo and feeder cells enhance embryo development better than the embryos cultured in presence of feeder cells without a direct contact [18]. Besides, this assumption may be true if the negative conditioning hypothesis was neglected.…”
Section: Discussioncontrasting
confidence: 59%
“…The most ordinary methods are the improvement in culture components and conditions [10,11], using sequential culture media [12], and conditioned media [13,14], and often feeder cells [15,16]. Many investigators suggest coculture systems could improve embryo quality and in vitro cleavage rate efficiently [15,[17][18][19]. While, few studies have reported no improvement in the embryo quality and implantation rates following co-culture of embryos with somatic feeder cells [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…2001; Johnson et al. 2008; Omar Farouk and Vlad 2008). Recently, CC co‐culture systems have been designed to support in vitro development of embryos in several species, including mice, cattle and humans (Parikh et al.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, CC co‐culture systems have been designed to support in vitro development of embryos in several species, including mice, cattle and humans (Parikh et al. 2006; Omar Farouk and Vlad 2008; Goovaerts et al. 2009).…”
Section: Discussionmentioning
confidence: 99%
“…We suspect that optimizing our technique would not only improve the percentage of two-cell embryos generated, but also show recognizable differences between using cryopreserved versus fresh gametes. One possible improvement to conventional IVF would be to maintain cumulus cell presence during culture, as this has been demonstrated to improve in vitro embryo development [26], [27] and fertilization efficiency [28][31]. One study found that the presence of an intact cumulus layer on oocytes increased the in vitro fertilizing ability of fresh capacitated mouse spermatozoa, with <10% of cumulus-free oocytes from GM female mice inseminated, compared to almost 40% two-cell embryos with COCs [28] Because cumulus cells must be removed for rapid and effective zona perforation, we decided to also remove cumulus cells for conventional IVF, to avoid this as a possible confounder.…”
Section: Discussionmentioning
confidence: 99%